(3Gdjef eGHjf GdOhdI GdehMOI hGdOhdI GdajOQGdjI QDjI eSJbHdjI (B:s (3OQGSI ebGQfI (B/s - (3UGdM Ydj Ydj GdHOhjs; (3QCaJ EHQGgje ahOIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3JCJj gPg GdQSGdI GdYdejI aj GdebGe GdChd ddOaGY Yf GdhMOI GdjefjI, hPdc HJHfj fXGe GddGeQcRjI GdEOGQjI hGdSjGSjI (B- (3GdfXGe GdajOQGdj HYO aTd GdfXGe GdeQcRj aj GdMaGX YdjgG(B. (3ceG JgOa dEjLGO Md efWbi ddNQhL ef MGdI GdGSJHOGO GdSjGSj hYOe GdGSJbQGQ GdPj YGfJ efg Gdjef hdGRGdJ JYGfj, hPdc Yf WQjb JbSje GdSdWI hJhRjY GdKQhI GdJj HSHHgeG Xd Gdjefjhf aj UQGY OGFe HGdEVGaI Edi Pdc LGAJ gPg GdQSGdI ddhUhd Edi QDjI efWbjI hYedjI dEfgGA GdMQH GdCgdjI GdeSJYQI, hEjLGO JShjI SjGSjI YGOdI JVef ddHdGO GdNQhL GdCef, hJVY Gdjefjjf Ydi HOGjI GdWQjb GdUMjMdHfGA Gdjef GdLOjO GdehMO GdPj jJWdYhf Edjg, hEbGeI OhdJge GdbGFeI Ydi GdYOGdI hGdOjebQGWjI hGdMQjI hGdeSGhGI aj Xd GdfXGe hGdbGfhfs
This thesis comes primarily to defend Yemeni unity, by adopting the administrative and political decentralization system the federal system after the failure of the central system to preserve it. It also aims to find a logical solution to get out of the state of political tyranny and instability that Yemen has suffered and is still suffering from, by dividing power and distributing wealth, because of which Yemenis have been in constant conflict. In addition, this message came to reach a logical and practical vision to end the raging civil war, find a just political settlement that guarantees the country a safe exit, and puts Yemenis on the right path to building the new, unified Yemen they aspire to, and the establishment of their state based on justice, democracy, freedom and equality under the regime. And the law
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdOhdj (B2022s
(3HHdjhLQGajG(B: (3UaMGJ (B492-529s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3Gdjefs; (3GdOhdI GdehMOIs; (3GdOhdI GdajOQGdjIs; (3GdfXGe GdehMOs; (3GdeedcI GdeJhcdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs